The Fiscal Impact of the Shift from Equity to Adequacy in School Finance Litigation - Forbis Jordan; Teresa Jordan; Kevin Crehan (Educational Considerations, 2004)
The focus of this study is a comparison of the changes in a set of state-level funding variables in state school finance programs for five groups of states with regard to high court decisions rendered during the 1970-1987 period and the 1988-2004 period.